Fractional-delay-resilient receiver design for interference-free MC-CDMA communications based on complete complementary codes - Liu, Zilong (2015)
Complete complementary codes (CCC) refer to a set of two-dimensional matrices which have zero non-trivial aperiodic auto- and cross- correlation sums. A modern application of CCC is in interference-free multicarrier code-division multiple-access (MC-CDMA) communications. In this paper, we first show that in asynchronous “fractional-delay” uplink channels, CCC-MC-CDMA systems suffer from orthogonality loss which may lead to huge interference increase when a conventional correlator based receiver is deployed. Then, by exploiting the correlation properties of CCC, we present a fractional-delay-resilient receiver which is comprised of a chip-spaced correlating array. Analysis and simulations validate the interference-free achievability of the proposed CSCA receiver in strong interference scenarios.